Investigating The Fracture Characteristics Of Nigerian Rice Husk Ash (Rha) - Based High Strength Concrete (Hsc) (2020)
Based on the initial research on the suitability of RHA in partial replacement of cement in HSC production, it was observed that between 10 - 20% replacement by weight of cement with RHA shows potential for use in the production of HSC based on their compressive strength. However, However, the use of compressive strength criteria only as a determinant in High Strength Concrete (HSC), especially in RHA-Cement blend concrete, has shown its inadequacies. Fracture Mechanics is a reliable experimental/analytical tool that has not been adequately used in the study of RHA-based HSC. Thus, the need to study its fracture mechanics parameters such as Crack Tip Opening Displacement (CTODC) test and Stress Intensity Factor (KSIC) to understand the behaviour of the RHA-based HSC to fracture toughness which is an indication of the strength of concrete when subjected to loading. Milled samples of the RHA were used in the preparation of RHA- Cement blends with the cement being replaced at 0%, 10% and 20% by cement weight. The 0% replacement served as a control for the experiment. 36 cubes of HSC with an expected compressive strength of 60MPa respectively were produced; 12 cubes for each percentage replacement aimed at affirming the compressive strengths were within the expected 60 MPa value. Then same mix design was used to prepare 78 beams (18, 30 and 30 for 0%, 10% and 20% RHA-Cement blend HSC) were prepared and subjected to experimental Fracture Mechanics three-point bending tests (TPBT) while the peak load for each beam before failure were recorded. The recorded peak loads were used to develop function via numerical computational and statistical models to determine the and values for the concrete. Based on the numerical analysis done, there was a progressive increase in CTODC and KSIC with an increase in RHA content in the concrete mixes with 20% having the highest C T OD c and Kfc (1 .4 1 9 7 M P aVm and 0 .0 3 1 7 m m) values compared to the control and the 10% RHA. Thus, it implies 20% RHA-cement blended HSC has more resilence compare to the 10% RHA.